Perancangan Sekolah Luar Biasa Tunarungu Di Siak Dengan Pendekatan Deafspace Guidelines - Agustina Irfita; Pedia Aldy; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Special school for the deaf in Siak is an children educational facility with hearing impairment in siak. Deaf limitations in impairment of hearing or in receiving information verbally make vision a major factor in information gathering. The design of special deaf schools in Siak is very necessary because the special schools in siak are still mixed which is serving many categories of people with disabilities so that the design and special educational facilities for deaf children are not prioritized especially in paying attention to the character and behavior of the deaf. In this case, the design of special deaf schools uses the behavior mapping method of person-center maps in observing deaf behavior and the application principle of deafspace guidelines as design ideas namely, space and proximity, sensory reach, mobility proximity, light and color, accoustics. Through the concept of deaf character building can meet the needs of the deaf in accordance with the patterns of behavior and character of the deaf in terms of personality, language, physical and emotional and social aspects.Keywords: Siak, Special Schools, Deaf, Deafspace Guidelines